LEARNING STRATEGIES OF AL-QUR'AN AND HADITH TEACHERS IN IMPROVING THE ABILITY TO READ THE QUR'AN AT ISLAMIC SENIOR HIGH SCHOOL 1 (MAN 1) MAKASSAR - Muh. Rahmat Hidayat; Ulfiani Rahman; M. Rusdi T (JICSA : Journal of Islamic Civilization in Southeast Asian, 2022)
The objectives of this research are describe the description of the ability to read the Koran of students at MAN 1 Makassar as well as describe learning strategies of Al-Qur'an Hadith teachers in improving students ' reading skills of Al-Qur'an at MAN 1 Makassar. This research is a type of field research with a qualitative approach. Data collection methods used are observation, interviews, and documentation. The data analysis technique starts from data collection, data reduction, data presentation and drawing conclusions. Checking the validity of the data using the triangulation method. The results of this study show that The ability to read the Qur'an of students at MAN 1 Makassar is indeed quite low. There are still many students who have difficulty reading the Qur'an , stammering in reading the Qur'an and are still wrong in pronouncing the letters or in the laws of reading. Besides it, The strategy that the teacher uses in an effort to improve the students ' ability to read the Qur'an is that the teacher conducts additional lessons outside of school hours, starting at 2 to 3 in the afternoon.